IMPLEMENTARY COMMUNICATION REGARDING THE POLICY OF ARTICLE 18 PARAGRAPH 9 IN THE REGULATION OF THE MINISTER OF EDUCATION, CULTURE, RESEARCH AND TECHNOLOGY NUMBER 53 OF 2023 BY UNIVERSITIES - Sagita Intan Cahyany; M. Syukron Anshori (Jurnal Impresi Indonesia, 2024)
The successful implementation of the policy of the Minister of Education, Research and Technology Regulation Article 18 Paragraph 9 Number 53 of 2023 is influenced by the delivery of information and communication by policy actors. By applying policy implementation theory, this research will examine the factors that influence the dimensions of communication, such as communication distribution, clarity of information, and consistency, and then provide a better understanding of the importance of communication in building cooperation in higher education programs, providing input and recommendations for legislators. Moreover,And other educational institutions are increasing information dissemination efforts and expanding the scope of their programs. This research aims to determine how implementers carry out information implementation, clarity, and consistency through communication studies. The research used is qualitative with a descriptive approach carried out through observations and interviews for three months at three universities in Sumbawa Regency with informants determined through purposive sampling, intended to provide an accurate picture of a particular situation or the relationship between various actual phenomena. Regularly. Information has been provided, but the implementation still needs to run optimally; this can be seen from the uneven delivery of information to technical implementers. The provision of information could have been better. Namely, the central institution still needs to conduct direct outreach to the targets or target objects by implementing technical UPTs. Meanwhile, academic parties at the University are waiting while studying the aims and objectives of the policy. It is hoped that central institutions will optimize the delivery of information and communication.